High-entropy functional materials - Gao, Michael C.; Miracle, Daniel B.; Maurice, David; Yan, Xuehui; Zhang, Yong; Hawk, Jeffrey A. (Journal of materials research, 2018)
While most papers on high-entropy alloys (HEAs) focus on the microstructure and mechanical properties for structural materials applications, there has been growing interest in developing high-entropy functional materials. The objective of this paper is to provide a brief, timely review on select functional properties of HEAs, including soft magnetic, magnetocaloric, physical, thermoelectric, superconducting, and hydrogen storage. Comparisons of functional properties between HEAs and conventional low- and medium-entropy materials are provided, and examples are illustrated using computational modeling and tuning the composition of existing functional materials through substitutional or interstitial mixing. Extending the concept of high configurational entropy to a wide range of materials such as intermetallics, ceramics, and semiconductors through the isostructural design approach is discussed. Perspectives are offered in designing future high-performance functional materials utilizing the high-entropy concepts and high-throughput predictive computational modeling.